(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The design of the pavement layers to be laid over sub grade soil starts off with the estimation of sub grade strength and the volume of traffic to be carried. Design of the various pavement layers are very much dependent on the strength of the sub grade soil over which they are going to be laid. Sub grade strength is mostly expressed in terms of CBR (California Bearing Ratio). Weaker sub grade essentially requires thicker layers whereas stronger sub grade goes well with thinner pavement layers. The sub grade is always subjected to change in saturation level due to precipitation, capillary action, flood or abrupt rise or subsidence of water table. Change in moisture level in sub grade causes change in the sub grade strength. And it becomes quite essential for an engineer to understand the exact nature of dependence of sub grade strength on moisture variation. An understanding of the dependence of the CBR strength of local soils on water content will contribute towards better design and maintenance practices. Normally CBR test is an easy and well adopted method conducted on soil samples to measure the strength of sub grade. However, many other tests are also considered for assessing the sub grade strength. The strength of soil, used for sub grade may vary largely on the amount of saturation in it, i.e. amount of water exposed to the soil. Hence, in this study an attempt has been made to vary the degree of soaking and hence the saturation level in various types of soils and study the engineering properties of soils including CBR at different saturation levels. It is observed that for fine grained and clayey soil, worst engineering properties are observed after three days of soaking.